Interpretación de los procesos adaptativos de la doble migración (migración-retorno) de un sistema familiar (2023)
This research aims to interpret the narratives of a family system in the face of its adaptive and emotional processes experienced in its double migration (migration-return (autonomous migration)) from a view of systemic psychological theory, through a qualitative - descriptive methodology based on the narratives of a family system composed of three people who play the roles of mother and children, respectively, who experienced the adaptive process in their double migration to the United States; this is done through in-depth virtual interviews, since the participants are abroad.